THE PRAGMATIC TRANSMISSION OF CONNOTATIVE MEANING IN LITERARY TEXTS: SPEECH ACTS, PRESUPPOSITION AND THE FOUR-COMPONENT MODEL - Sayliyeva Mokhinur Rakhmiddinovna (International Journal of Literature and Language Studies, 2026)
This article analyses the pragmatic foundations on which connotative meaning is transmitted in English and Uzbek literary texts. It argues that connotation in literary discourse is shaped pragmatically within the communicative relationship among author, text and reader, and that it often arises not from encoded meaning but from the inference the reader draws on the basis of cooperation, context and shared knowledge. Drawing on the speech-act theory of Austin and Searle, the discourse-marker theory of Schiffrin, the relevance theory of Sperber and Wilson, and the presupposition theories of Karttunen and Stalnaker, the study identifies the pragmatic categories proposition, reference, explicature, inference, relevance and presupposition through which connotation is built. Applying Teliya's four-component model comprising emotive, evaluative, expressive and stylistic components to passages from Defoe's Robinson Crusoe, Hosseini's The Kite Runner and A Thousand Splendid Suns, and Mitchell's Gone with the Wind, the article demonstrates that these components operate not in isolation but in interaction, with one usually dominant and the others auxiliary. It further shows that delayed perlocutionary effects and hybrid speech acts play an important role in the transmission of literary connotation.